Balancing Act: Navigating Oxidative Stress in Pregnancy for Optimal Health - Lateef Hubeni, Israa; K. Hummadi, Wisam; Saad Jwad, Rasha (Al-Nahrain Journal of Science, 2026)
Oxidative stress refers to a state of balance involving the generation of reactive oxygen species (ROS) and the body's capacity to counteract their harmful effects. ROS are naturally occurring molecules that, if not adequately regulated, can damage cells and tissues if not properly managed. During pregnancy, ROS levels fluctuate and play a role in various developmental processes. However, an excessive accumulation of reactive oxygen species can lead to oxidative stress, which is linked to numerous complications during pregnancy.